"What Just Happened to My Residency?" The Effect of the Early Coronavirus Disease 2019 Pandemic on Colorectal Surgical Training. Issue 5 (10th February 2021) - Columbus, Alexandra B.; Breen, Elizabeth M.; Abelson, Jonathan S.; Kuhnen, Angela H.; Kleiman, David A.; Marcello, Peter W.; Roberts, Patricia L.; Saraidaridis, Julia T.
Abstract : Supplemental Digital Content is available in the text.